2010
DOI: 10.1038/sj.bjc.6606040
|View full text |Cite
|
Sign up to set email alerts
|

The effect of self-sampled HPV testing on participation to cervical cancer screening in Italy: a randomised controlled trial (ISRCTN96071600)

Abstract: Background:In Italy, cervical cancer screening programmes actively invite women aged 25–64 years. Programmes are hindered by low participation.Methods:A sample of non-responder women aged 35–64 years, belonging to three different programmes (in Rome, Florence and Teramo), was randomly split into four arms: two control groups received standard recall letters to perform either Pap-test (first group) or human papillomavirus (HPV) test (second group) at the clinic. A third arm was sent letters offering a self-samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 36 publications
3
77
3
Order By: Relevance
“…Giorgi‐Rossi et al . invited Italian women for opt‐in self‐sampling if they had not responded to a routine invitation for 3–5 months 13, 14. Here, 20% women participated when offered to have the kit sent to home and 9–11% when they could pick it up from a local pharmacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Giorgi‐Rossi et al . invited Italian women for opt‐in self‐sampling if they had not responded to a routine invitation for 3–5 months 13, 14. Here, 20% women participated when offered to have the kit sent to home and 9–11% when they could pick it up from a local pharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach is to have nonattenders actively “opt in,” that is, order the self‐sampling kits if interested after receiving an invitation from the screening program. Only few studies11, 12, 13, 14, 15, 16 have used the opt‐in approach so far, with a reported return rate of 9–39%. A general concern is that by requiring additional effort from women to confirm their willingness to participate, this approach is vulnerable to low participation rates 13, 14…”
mentioning
confidence: 99%
“…In trials, the response rate among underscreened women who received invitations, including self-samplers, varied widely between settings ranging from 6% (8) to 31% (9), which was on average 2.1 times higher (95% CI, 1.3-3.5) than in the control groups who received a conventional reminder letter (4). In two trials, conducted in Italy and Sweden, women were sent a self-sampler if they confirmed their wish to receive one (10,11). The pooled difference in participation rates between the opt-in self-sampling arm and the control arm of conventional reminder letter was not significantly different from zero (1%; 95% CI, À4% to 5%; pooled from refs.…”
mentioning
confidence: 99%
“…14 However, further evaluation of this approach is needed as past studies suggest that women's preference for self-sampling at home or at the clinic might vary across settings. 18-20 For instance, in a Uganda study, lack of privacy at home was cited as a barrier to self-sampling. 19 In Italy, direct mailing of a self-sampling kit to women who failed to respond to a screening invitation increased screening coverage in urban areas, but not in rural areas.…”
Section: Discussionmentioning
confidence: 99%